Prevalence of dog bite and its associated factors among public primary schools students in Madawaki district Gusau, Nigeria - Ibrahim, Hassan (2020)
Dog bite is a global public health problem that is sometimes fatal, due to infection from rabies and this rabies constitute 30% to 50% of this fatality in children, especially 5 to 14 years old. Dog bite is a major source of animal bite injuries in low-income countries such as Nigeria, where 55.7% prevalence of dog bite was reported. Gender and dog ownership are some of the associated factors of dog bite. Despite its prevalence, there is scarcity of research on the prevalence and its associated factors in the northern part of the country. The objectives of this study were to determine the prevalence of dog bite and its associated factors among public primary schools students in Madawaki district Gusau, Nigeria. A cross-sectional study was conducted among 1,226 public primary school students aged between 11 to 13 years old, in Madawaki district of Gusau, Zamfara State, Nigeria. In order to select 1,226 eligible participants, out of 4200, stratified sampling technique with unequal proportion was conducted with stratification to urban (4 schools) and semi-urban (3 schools). Self- administered questionnaire was used to report dog bite history, sociodemographic characteristics, knowledge on interaction with dog, knowledge on implication of dog bite to health, dog ownership by the family, dog ownership by neighbour and risk behaviours among public primary schools students in Madawaki district from November 2018 to May 2019. Descriptive analysis, chi-square test, simple and multiple binary logistic regression analysis were conducted, and the level of significance was set at α = 0.05. Majority of the respondents were male (53.2%) and Hausa ethnic group (83.2%). The distribution of respondents by urban, semi urban and rural residential areas was 51.3%, 19.0% and 29.7% respectively. The prevalence of dog bite was 54.5%. Gender, knowledge on interaction with dog, risk behaviours, dog ownership by family and dog ownership by neighbours are significantly associated with dog bite. In the multiple binary logistic regression analysis, the factors of dog bite among respondents were male (AOR = 2.252; Cl = 1.719, 2.949), score for knowledge on interaction with dog (AOR = 0.884; Cl = 0.858, 0.911), score for risk behaviours of children (AOR = 1.020; Cl =1.004, 1.035), dog ownership by the family of the respondents (AOR =1.456; Cl =1.089, 1.946) and dog ownership by the neighbours of the respondents (AOR = 1.752; Cl = 1.334, 2.303). More than half of the public primary schools students in Madawaki district had history of dog bite, male have experienced dog bite more than the female. Decrease in knowledge score, high score in risk behaviours, gender, owning dog by family or neighbours are responsible for the high burden of this dog bite. Hence, there is a need for awareness and improve knowledge towards prevention programme, towards dog bite in Madawaki district, and to educate the dog owners.